Management of biliary obstruction in patients with newly diagnosed alveolar echinococcosis: a Swiss retrospective cohort study - Sandra Müller; Soleen Ghafoor; Cordula Meyer zu Schwabedissen; Felix Grimm; Fritz Ruprecht Murray; Lars Husmann; Nadine Stanek; Peter Deplazes; Christoph Schlag; Andreas E. Kremer; Christoph Gubler; Cäcilia S. Reiner; et al. (Swiss Medical Weekly, 2023)
BACKGROUND AND STUDY AIMS: Alveolar echinococcosis, an orphan zoonosis affecting the liver, is of increasing concern worldwide. Most symptomatic cases present at an advanced and inoperable stage, sometimes with biliary obstruction prompting biliary tract interventions. These are, however, associated with a high risk of infectious complications. The aim of this retrospective study was to compare the effectiveness and safety of conservative and interventional treatment approaches in patients with newly diagnosed alveolar echinococcosis and biliary obstruction.